PELAKSANAAN STANDAR OPERASIONAL PROSEDUR CLEANING SERVICE DI RAUN-RAUN FOODPARK PEKANBARU - Ferdian, Simon Faris; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study examines the implementation of Standard Operating Procedures (SOPs) by public area attendants at the Raun-Raun family and culinary tourist destination in Pekanbaru City, Riau Province. Using qualitative descriptive methods, this study aims to explore how SOPs are implemented in various public areas, such as the café garden, tenant areas, restrooms, live music, prayer rooms, and parking. The results indicate that SOPs are routinely implemented with adjustments to field conditions, both in writing, verbally, and through digital media such as WhatsApp. These SOPs are flexible, encompassing daily routines and situational conditions that arise in the field. It was found that employee knowledge of SOPs is influenced by training, work experience, and direct direction from supervisors. This study suggests the need to strengthen the overall understanding of SOPs to ensure optimal and consistent public service in tourist areas. Keywords: Raun-Raun, Standard Operating Procedures, Cleaning Service, Public Area Attendant, Tourist Destination